1992
DOI: 10.1051/rnd:19920403
|View full text |Cite
|
Sign up to set email alerts
|

Follicular dynamics, plasma metabolites, hormones and insulin-like growth factor I (IGF-I) in lactating cows with positive or negative energy balance during the preovulatory period

Abstract: Summary ― The effect of dietary energy balance (EB) on growth of ovarian follicles was tested. Cows (n = 9) were fed a high energy diet (HE diet; positive EB; n = 4) or switched to a low energy diet (LE diet; negative EB; n = 5) during the preovulatory period. Non-esterified fatty acids (NEFA) were greater in cows fed the LE diet. Concentrations of luteinizing hormone (LH) were similar in HE and LE cows. However, the growth of preovulatory follicles in cows fed the LE diet was 50% that of cows fed the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1
7

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 13 publications
(12 reference statements)
2
37
1
7
Order By: Relevance
“…Richards et al [72] observed that circulating concentrations of LH and IGF-I decreased during feed restriction of non-pregnant beef cows and suggested that these responses might be linked physiologically. Lucy et al [55] observed a positive correlation between the estrogen-progesterone ratio in follicular fluid and plasma IGF-I, suggesting an effect of plasma IGF-I on follicular development. Moreover, an association has been reported between twinning rates in cattle and concentrations of both serum and follicular fluid IGF-I.…”
Section: Igf-i and Hypothalamo-pituitary Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Richards et al [72] observed that circulating concentrations of LH and IGF-I decreased during feed restriction of non-pregnant beef cows and suggested that these responses might be linked physiologically. Lucy et al [55] observed a positive correlation between the estrogen-progesterone ratio in follicular fluid and plasma IGF-I, suggesting an effect of plasma IGF-I on follicular development. Moreover, an association has been reported between twinning rates in cattle and concentrations of both serum and follicular fluid IGF-I.…”
Section: Igf-i and Hypothalamo-pituitary Functionmentioning
confidence: 99%
“…However, in a later study McGuire et al [57] reported for the first time that in two days of feed deprivation, circulating concentrations of IGF-I reduced by 50% in lactating cows. Spicer et al [83] reported that short-term fasting in heifers decreased plasma IGF-I, and Lucy et al [55] found that cows fed low energy diets had lower plasma IGF-I. In suckled and/or non-pregnant beef cows, feed restriction resulted in a marked depression in serum concentrations of IGF-I, whereas insulin and glucose were only depressed slightly [72,74].…”
Section: Effect Of Nutritional Status On Circulat-ing Concentrations mentioning
confidence: 99%
“…Some suggestions can be made since glucose and insulin are increased after feeding extra glycogenic nutrients and are suggested as positive metabolic signals to the reproductive axis [11,13,19,57,118,135]. Plasma NEFA and BHBA levels are increased after feeding extra lipogenic nutrients and associated with decreased reproductive performance and anestrous [9,65,[136][137][138]. Both observations might imply that the C2/C3 compound balance is important for reproductive performance.…”
Section: Effect Of Lipogenic and Glycogenic Nutrients On Reproductivementioning
confidence: 99%
“…Other studies reported that IGF-I concentrations in blood of cows in cNEB due to either fasting or lactating were lower compared to animals in a less negative cNEB [63,104] and that cows selected for high milk production, thereby more at risk of non adaptation, have lower insulin concentrations during peak and mid lactation [10]. Although there are also less promising studies, IGF-I seems one of the reasonable candidates for possible fertility disturbance due to non adaptation.…”
Section: A Role For Insulin and Igf-i On Ovarian Functionmentioning
confidence: 99%
“…Because the amount of stored body fat and the mobilization of fat is reflected in blood leptin concentrations, changes with regard to the concentration of this hormone in early lactation can be anticipated too [9,33]. Other hormones that tend to decrease during feed restriction and NEB are thyroid hormones [65] and insulin-like growth factors (IGF) [63]. These changes reflect the adaptational system of the cow which is activated in order to meet the demands for the increasing milk production and maintenance.…”
Section: Negative Energy Balance and Adaptation: Definition Quantifimentioning
confidence: 99%